NICCOLO RIDOLFI AND THE CARDINAL'S COURT politics, patronage and service in sixteenth-century italy. - Byatt, Lucinda ([S.l.] : ROUTLEDGE, 2022)
Niccol Ridolfi (1501-50), was a Florentine cardinal, nephew and cousin to the Medici popes Leo X and Clement VII, and he owed his status and wealth to their patronage. He remained actively engaged in Florentine politics, above all during the years of crisis that saw the Florentine state change from republic to duchy. A widely respected patron and scholar throughout his life, his sudden death during the conclave of 1549-50 led to allegations of poison that an autopsy appears to confirm. This book examines Cardinal Ridolfi and his court in order to understand the extent to which cardinalate courts played a key part in Rome's resurgence and acted as hubs of knowledge located on the fault lines of politics and reform in church and state, hospitable spaces that can be analysed in the context of entanglements in Florentine and Roman cultural and political patronage, and intersections between the princely court and a more professional and complex knowledge and practice of household management in the consumer and service economy of early modern Rome. Based on an array of archival sources and on three treatises whose authors were closely linked to Ridolfi's court, this monograph explores these multidisciplinary intersections to allow the more traditional fields of church and political history to be approached from different angles. Niccol Ridolfi and the Cardinal's Court will appeal to all those interested in the organisation of these elite establishments and their place in sixteenth-century Roman society, the life and patronage of Niccol Ridolfi in the context of the Florentine exiles who desired a return to republicanism, and the history of the Roman Catholic Church.
Keywords: HISTORY / Europe / Italy; HISTORY / Social History; HISTORY / Renaissance; Ridolfi, Niccolò, -- 1501-1550; Catholic Church -- Italy -- History -- 16th century; Florence (Italy) -- Politics and government -- 1421-1737.